Virtual Field Trip: A study to analyse the raising awareness of biodi-versity loss through biodiversity analyses in Virtual Reality - Nina Heuke genannt Juergensmeier; René Schmidt; Britta Stumpe (European Journal of Geography)
Biodiversity loss poses a significant threat to global ecosystems, with human activities driving extinction at an increasing rate. Despite international agreements such as the Convention on Biological Diversity and the Biodiversity Strategy 2030, biodiversity continues to decline. Education about biodiversity is therefore of crucial importance, mainly as part of teacher education. This study examined the effectiveness of Virtual Field Trips (VFTs) in university-based geography teacher education to raise awareness of biodiversity loss. Therefore, two study groups, the experimental group (EG) and the control group (CG), participated in a quasi-experimental longitudinal study. The EG carried out a VFT as an intervention in which two different ecosystems in Berlin, Germany, were experienced and analysed in terms of biodiversity. With a pre-test and post-test, we examined if the VFT as an intervention affects the EG. The results show no significant differences between the groups after the intervention. However, high mean values for most of the questionnaire scales can already be found for both groups in the pre-test. Likewise, the EG showed intrinsic motivation after the intervention based on the VFT, indicating its potential in education.